Child supplementary feeding from primiparas’ point of view - Mirna Albuquerque Frota; Ana Thamiris Tomaz Sousa; Cíntia Freitas Casimiro; Ivna Silva Andrade; Vanessa Gomes Silveira (Revista Brasileira em Promoção da Saúde, 2013)
Objective: To investigate mothers’ knowledge of infant feeding. Methods: Descriptive study with a qualitative approach, developed in a Primary Health Unit located in the city of Maranguape-CE, with 14 first-time mothers of children aged 6 to 24 months, who were receiving complementary feeding and were resident in the District of Tabatinga between the months of July and October 2009, through participant observation and semi-structured interview. After reading, careful description of the interviews and classification of speech, the following categories emerged: complementary feeding and breastfeeding; food offered to children; and determinants of the healthy infant feeding. Results: Although mothers have basics knowledge of how a healthy diet should be, they continued introducing harmful foods to children, showing lack of control over food education. Mothers are aware that feeding the child could be based on nutritious foods; nevertheless, they prefer choosing those that feature ease of supply. Conclusion: The introduction of new foods was performed incorrectly and nutritional quality is inadequate for children. The mother appears in charge of the child development; however, for this process to be successful, she must become conscious of this subject, since a healthy diet directly influences the child’s organism, as it acts in all body systems.